2019
DOI: 10.1111/cdoe.12507
|View full text |Cite
|
Sign up to set email alerts
|

Changes in young children's oral health‐related behaviours and caregiver knowledge: A cluster randomized controlled trial in Brazil

Abstract: ObjectiveTo evaluate the effectiveness of an intervention to improve young children's oral health‐related behaviours and caregiver knowledge.MethodsThis paper reports on findings from a cluster randomized controlled trial, 12 months after of baseline, conducted in Pelotas, Southern Brazil. Two Primary Healthcare Centers (PHCs) and 170 caregiver‐child dyads were assigned to an intervention group, and two PHCs and 174 dyads were assigned to a control group. Children's oral hygiene behaviours, sugar consumption a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…As for the frequency of brushing, there was an increase pre-and post-intervention in the MI group for the number of children who had their teeth brushed 03x / day. Similar results were also exposed by Menegaz et al (2020), whose work indicated an increase in the brushing frequency of 02x or more with an absolute difference of 30.5 % for the MI group. In a randomized clinical trial on the influence of MI in preventing early childhood caries involving 1065 children and their caregivers, there was no significant difference between group interaction versus time for brushing frequency.…”
Section: Discussionsupporting
confidence: 78%
“…As for the frequency of brushing, there was an increase pre-and post-intervention in the MI group for the number of children who had their teeth brushed 03x / day. Similar results were also exposed by Menegaz et al (2020), whose work indicated an increase in the brushing frequency of 02x or more with an absolute difference of 30.5 % for the MI group. In a randomized clinical trial on the influence of MI in preventing early childhood caries involving 1065 children and their caregivers, there was no significant difference between group interaction versus time for brushing frequency.…”
Section: Discussionsupporting
confidence: 78%
“…In 2020 Menegaz demonstrated how after practicing targeted educational programs in a Brazilian school, positive effects were found on behaviors related to the oral health of children and the knowledge of caregivers, improving the use of fluoride toothpaste in the right amount based on the 'age. 11 In a 2021 study, Andrew L., et al, reports how the lack of oral hygiene care in children not only reflects a lack of knowledge of the professional guidelines, but it is also the result of personal barriers or external constraints such as the emotional reactions of children that cannot be controlled (aversion of having a toothbrush or tooth paste in the mouth), or the manual skills required for proper oral hygiene are not exercised and reinforced. 28 Other external constraints can be a hectic lifestyle, with strict deadlines and schedules that take away needed time for personal care.…”
Section: Discussionmentioning
confidence: 99%
“…10 Tooth decay is N o n -c o m m e r c i a l u s e o n l y also the most common reason for 5-9-year-old British children admission to the hospital (Health and Social Care Information Centre (HSCIC), 2015). 11 Early Childhood Caries (ECC) prevalence in Italy, in 2019, was 8.2% overall, 2.9% in 0-23-month-old children, 6.2% in 24-47-month-old children and 14.7% in 48-71-monthold children (p for trend<0.001). 4 The carious process starts when S. mutans, the principal bacterial component implicated in the initiation of dental caries, colonizes the oral cavity of infants/children following the eruption of primary teeth.…”
mentioning
confidence: 99%
“…In many countries early preventive dental care is generally not performed in preschool children; current literature reports that this is the result of several factors, including: lack of knowledge and awareness of the importance of primary teeth, parents’ dental fear and popular misconceptions about dental care [ 61 ]. Roberts & Codon reported how participants in a UK survey believe that oral health care is simple, common sense and something everyone knew, without considering the importance of being properly educated in this field [ 62 ].…”
Section: Home Oral Care Of Childrenmentioning
confidence: 99%